    # Factor Theorem Let p(x) be a polynomial of degree n ≥ 1 and a be any real number. Then by factor theorem, x � a is a factor of p(x), if p(a) = 0 and p(a) = 0, if x � a is a factor of p(x).

FACTORISATION OF THE QUADRATIC POLYNOMIAL OF TYPE x2 + lx + m:

For a quadratic polynomial of type x2 + lx + m, where l, m are constants, first we split the middle term lx as ax + bx so that ab = m, then we get

 x2 + lx + m = x2 + ax + bx + ab = x(x + a) + b(x + a) = (x + a)(x + b)

FACTORISATION OF THE QUADRATIC POLYNOMIAL OF TYPE ax2 + bx + c:

For a quadratic polynomial of type axx2 + bx + c, where a ≠ 0 and a, b, care constants, first we assume that (px + q) and (rx + s) are its factors. Then we get,

 ax2 + bx + c = (px + q) (rx + s) = prx2 + (ps + qr)x + qs

Now comparing the coefficients of x2 on both sides we get,

a = pr

and comparing the coefficients of x on both sides we get,

b = ps + qr

Comparing the constant terms we get,

c = qs

Hence this implies that b is a sum of two numbers ps and qr, and the product of these two numbers (ps)(qr) = (pr)(qs) = ac.

Hence in order to factorise ax2 + bx + c, we have to write b as the sum of two numbers whose product is ac.

Example 1:

Using the factor theorem determine whether x + 1 is a factor of the polynomial 2x3 + x2 � 2x - 1 or not.

Solution:

Let p(x) = 2x3 + x2 � 2x � 1

Now x + 1 = 0 x = -1

 Hence p(-1) = 2(-1)3 + (-1)2 � 2(-1) � 1 = -2 + 1 + 2 � 1 = 0

Hence by factor theorem, x + 1 is a factor of p(x).

Example 2:

Factorise x2 � 5x + 6.

Solution:

Splitting the middle term we get:

 x2 - 5x + 6 = x2 � 3x � 2x + 6 = x(x � 3) � 2(x � 3) = (x- 3)(x � 2)            (Answer)

Hence by factor theorem, x + 1 is a factor of p(x).

Example 3:

Factorise 12x2 � 7x + 1.

Solution:

First we find the product of 12 so that the sum of the two numbers is 7. i.e., 12 = 4�3 (also 4 + 3 = 7)

 Hence 12x2 � 7x + 1 = 12x2 � 4x � 3x + 1 = 4x(3x � 1) -1(3x � 1) = (3x � 1)(4x � 1)        (Answer)

Example 4:

Find the values of p and q so that x + 2 and x - 1 are factors of the polynomial x3 + 10x2 + px + q.

Solution:

Let g(x) = x3 + 10x2 + px + q

Now given that x + 2 is a factor of g(x).

By factor theorem if x + 2 is a factor of g(x), then g(-2) = 0.

 Hence g(-2) = (-2)3 + 10(-2)2 + p(-2) + q = 0 = -8 + 40 -2p + q = 0 = 2p � q = 32                          (1)

Again if x � 1 is a factor of g(x), then g(-2) = 0.
g(1) = 0

 Hence (1)3 + 10(1)2 + p(1) + q = 0 => 1 + 10 + p + q = 0 => p + q = -11                          (2)

Adding (1) and (2) we get,

3p = 21
=> p = 7

Putting the value of p = 7 in (2) we get,
7 + q = -11
=> q = -18

Hence p = 7 and q = -18               (Answer)

If you are stuck with a Factorization Quadratic Polynomial Homework problem and need help, we have excellent tutors who can provide you with Homework Help. Our tutors who provide Factorization Quadratic Polynomial help are highly qualified. Our tutors have many years of industry experience and have had years of experience providing Factorization Quadratic Polynomial Homework Help. Please do send us the Factorization Quadratic Polynomial problems on which you need Help and we will forward then to our tutors for review.

Online Tutor Factor Theorem:

We have the best tutors in math in the industry. Our tutors can break down a complex Factor Theorem problem into its sub parts and explain to you in detail how each step is performed. This approach of breaking down a problem has been appreciated by majority of our students for learning Factor Theorem concepts. You will get one-to-one personalized attention through our online tutoring which will make learning fun and easy. Our tutors are highly qualified and hold advanced degrees. Please do send us a request for Factor Theorem tutoring and experience the quality yourself.

Other topics under Number Theory:       • 